Influence of microwave sintering on electrical properties of BCTZ lead free piezoelectric ceramics. Issue 4 (April 2020) - Orlik, Kelly; Lorgouilloux, Yannick; Marchet, Pascal; Thuault, Anthony; Jean, Florian; Rguiti, Mohamed; Courtois, Christian
Abstract: Barium titanate doped with calcium and zirconium (BCTZ) could be used at low temperature to replace lead based piezoelectric ceramics (PZT). The classical way to obtain BCTZ is the solid-state route coupled with conventional sintering, but this step is time-consuming. To reduce the duration of this process, microwave heating was used for sintering. It is a fast sintering method and the heating rate was around 200 °C/min in this study. Slightly better electrical properties with finer microstructures (d33 * = 706 pm/V, grain size about 42.1 ± 14.2 μm) were obtained for samples sintered by microwave heating during 50 min compared to the conventional sintering (d33 * = 622 pm/V, 22.6 ± 4.4 μm). The main result of this study is that by using microwave heating, the sintering step duration (including heating, dwell time and cooling) was drastically reduced: 1.5 h for microwave sintering against 12.5 h for conventional sintering.